Circulating Circular RNAs: Novel Biomarkers for Heart Failure - Sun, Chuan; Ni, Mingming; Song, Bo; Cao, Lu (Frontiers in Pharmacology, 2020)
Heart failure (HF) is a serious, chronic disease-causing significant ill health and high mortality worldwide. The current clinical strategies emphasize reducing the transition from a healthy to a failing heart, despite the shift in the clinical goal from healing to disease prevention. Recent research advancements on non-coding RNAs (ncRNAs) have demonstrated that circular RNAs (circRNAs) are significant therapeutic targets in HF. Previous studies have highlighted the potential applicability of circRNAs in the diagnosis and treatment of diseases. However, less is known regarding the potential benefits of circRNAs as novel diagnostic and treatment biomarkers for HF. In the present study, we summarize the current developments and achievements associated with the use of circRNAs as HF biomarkers. We also discuss future research directions regarding HF diagnosis and treatment.